Removal of COD and TSS From Dye Solution Using Sand Filtration and Adsorption - Heny Juniar; Muhammad Said; Sri Haryati; Muhammad Faizal (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2016)
Abstract: This research was conducted in order to obtain proper compositions and the standard condition for the simple filtration equipments and optimum operational conditions in adsorption column. The research was carried out by analyzing parameters COD and TSS. The result showed that the process was able to reduced parameters observed from filtration step until the process in adsorptions column. The optimum conditions for sand filter equipment were 10 cm sand height, at least 7 cm fibers, 3-4 cm gravel. In the adsorption column, the optimum conditions for green waste water were flow rate at 40 ml/min 60 min adsorptions time, and 60 cm bed height. While purple for waste water; 20 mL/min of flowrate, 60 min of adsorption time, and the 60 cm of bed heightKey words: dye solution, COD, TSS, sand filtration, adsorption column Abstrak (Indonesian): Penelitian mengenai pengolahan limbah cair hasil pencelupan benang songket dengan metode filtrasi dan adsorpsi telah dilaksanakan. Penelitian bertujuan untuk mendapatkan komposisi dan ukuran yang tepat bagi alat penyaring sederhana dan mendapatkan kondisi operasi yang tepat bagi kolom adsorpsi.  Parameter pengamatan adalah kadar COD dan TSS.  Hasil penelitian menunjukkan bahwa telah terjadi penurunan kadar limbah sejak tahap penyaringan hingga proses di kolom adsorpsi.  Kondisi optimum alat penyaring sederhana adalah ketebalan pasir 10 cm, ijuk minimal 7 cm, kerikil 3-4 cm dan penambahan tawas sebanyak 2g/L limbah.  Pada kolom adsorpsi kondisi optimum adalah kecepatan alir 40 mL/menit, waktu tinggal di kolom 60 menit dan ketinggian unggun batubara 60 cm.Kata kunci: limbah cair pencelupan, bahan-bahan berbahaya, filtrasi pasir, kolom adsorpsi